The effect of ice gel pack on pain reduction of sheath removal in post-cardiac catheterization patients - Prasetya, Arif; Handian, Feriana Ira (The Journal of Palembang Nursing Studies, 2023)
Background: Cardiac catheterization is a minimally invasive intervention that can cause complications of vascular access after compression of the femoral artery or sheath removal. Cold pack gel is a non-pharmacological therapy given after sheat removal to reduce pain. Objective:This study aimed to measure the effect of ice pack gel on pain reduction in arterial sheath removal post-cardiac catheterization patients. Methods: This interventional clinical study with control and group treatment was conducted in the cardiology room of Saiful Anwar Hospital Malang, Indonesia. The respondents (n=32) were divided into two groups in pre and post-test control group design. Group A receives pressure bandages as a standard protocol (control groups) while group B, ice-packed gel. Pain scale measured by Visual Analog Scale (VAS) by 1-10. Results: The Mann-Whitney test in two groups shows that there are differences in scores of pain reduction. The pain reduction difference in the treatment group (ice pack gel) was higher than the control ones (p < 0.001). The cold temperature of the cold-packed gel decreased the peripheral free nerve ending conductivity, furthermore, it made sensitivity stimulus or pain impulses slowed down then reduced the perception of pain. Conclusions: The intervention of ice-packed gel is more effective than the standard protocols to reduce the pain in the removal sheath post cardiac catheterization.